AIS-driven vessel activity and emissions modelling for offshore decommissioning activities in the North Sea - Kate Gormley; Samuel R. Cauvin; Shahin Jalili; Malcolm Stone; Richard Neilson (Frontiers in Marine Science, 2026)
Introduction Maritime transport is a major source of air pollutants yet remains one of the least regulated sectors globally. In the North Sea, vessel activity associated with offshore energy infrastructure decommissioning is expected to increase over the next decade. However, vessel-specific emissions during these activities remain poorly quantified, with existing approaches relying largely on coarse-scale estimates. This study aimed to develop a data-driven, bottom-up methodology for estimating vessel emissions using Automatic Identification System (AIS) data to enable high-resolution spatial and temporal analysis of offshore energy-related shipping emissions. Methods A custom vessel-tracking tool was developed to process large AIS datasets collected between 2015 and 2021 for the northern North Sea. Vessel movements and operational patterns were reconstructed from AIS records, and emissions of carbon dioxide (CO 2 ), nitrogen oxides (NO x ), and sulphur dioxide (SO 2 ) were estimated based on vessel speed, operational activity, and engine characteristics. Emissions were spatially allocated to a 1 km 2 grid. The methodology was applied to three offshore decommissioning case study areas: Scott, Gannet, and Subsea, representing different infrastructure densities and operational stages within the marine energy sector. Sensitivity analyses were conducted to evaluate uncertainties associated with fuel consumption and auxiliary engine assumptions. Results Emissions were found to be highly localised around offshore installations and displayed strong temporal variability associated with episodic operational activity. Among the case study areas, Gannet exhibited the highest emissions intensity, contributing up to 5% of regional CO 2 emissions during peak operational periods. Correlations between vessel transits and emissions varied between sites, indicating that vessel counts alone do not adequately capture emissions behaviour. Operational modes such as idling and dynamic positioning were identified as important contributors to overall emissions. Sensitivity analysis demonstrated that assumptions relating to fuel consumption rates and auxiliary engine usage were key sources of uncertainty in the emissions estimates. Discussion The findings demonstrate that AIS-based bottom-up approaches can provide more accurate, transparent, and spatially resolved emissions estimates for offshore energy operations compared with conventional regional-scale methods. Incorporating operational vessel behaviour substantially improves emissions characterisation and highlights the importance of accounting for non-transit activities in offshore environments. This methodology has potential applications in emissions reporting, regulatory compliance, and decarbonisation planning for offshore energy systems undergoing transition and decommissioning.

Crop mixtures: yield responses to climate and management and impacts on seed and soil chemical composition in a Scottish-based study - R. Brooker; R. J. Pakeman; R. L. Hewison; C. Mitchell; A. C. Newton; R. Neilson; S. Raubach; P. D. Shaw; S. Verrall; A. J. Karley (Plant and Soil, 2026)
Introduction Crop mixtures can be an important part of the toolkit for maintaining crop production while addressing the climate and nature crises. However, uncertainties around some issues may prevent their uptake. Research question This study addressed several uncertainties, specifically the response of mixture yields to climate and management, and the impacts of mixed cropping on seed chemical composition, soil carbon and nutrients. Materials and methods We undertook 32 intercropping trials between 2020 and 2022 on both commercial and research farms. These varied in design, management and crop combinations, with mixture choice often determined by farmers. We assessed multiple responses including yield, weed cover, and seed and soil chemical composition. Results and conclusions When compared to monocultures, yield gains from growing a crop mixture were roughly 20% based on Crop Performance Ratio (CPR). We found limited impacts of mixture diversity and composition on seed chemical composition, influences of management on weed control, and enhanced crop mixture performance under cooler conditions with lower rainfall. We also found varying mixture performance depending on mixture composition. Importantly, irrespective of management, climate, and composition effects, crop mixtures always performed at least as well as expectations based on monocultures. Even without further refinement from, for example, targeted breeding, crop mixtures provide reliable crops without yield losses or (for parameters tested) substantial changes in seed chemistry. However, detected reductions in organic matter in upper soil layers indicate a priority for future research is understanding crop mixture impacts on soil carbon dynamics in both shallow and deep soils.

Aligning Evidence- based Recommendations to Improve Population Health - Opportunities for Nutrition Researchers and Practitioners - B. Kowtha; E. Neilson; E. Vogt; R. McNellis (Journal of the Academy of Nutrition and Dietetics, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Genesis of honeycomb buildups in the Permian Zechstein Group, Southern North Sea - Thomas D. Houghton; Joyce E. Neilson; John R. Underhill; Rachel E. Brackenridge (Marine and Petroleum Geology, 2024)

Bottom-up formulations for the multi-criteria decision analysis of oil and gas pipeline decommissioning in the North Sea: Brent field case study - Shahin Jalili; Georgios Leontidis; Samuel R. Cauvin; Kate Gormley; Malcolm Stone; Richard Neilson (Journal of Environmental Management, 2024)

The search for “Jenyon’s Channel”: The missing link between the Permian basins in the North Sea - Thomas D. Houghton; Rachel E. Brackenridge; Joyce E. Neilson; John R. Underhill (Marine and Petroleum Geology, 2024)

Environment and shipping drive environmental DNA beta‐diversity among commercial ports - Jose Andrés; Paul Czechowski; Erin Grey; Mandana Saebi; Kara Andres; Christopher Brown; Nitesh Chawla; James J. Corbett; Rein Brys; Phillip Cassey; Nancy Correa; Marty R. Deveney; et al. (Molecular Ecology, 2023)
The spread of nonindigenous species by shipping is a large and growing global problem that harms coastal ecosystems and economies and may blur coastal biogeographical patterns. This study coupled eukaryotic environmental DNA (eDNA) metabarcoding with dissimilarity regression to test the hypothesis that ship‐borne species spread homogenizes port communities. We first collected and metabarcoded water samples from ports in Europe, Asia, Australia and the Americas. We then calculated community dissimilarities between port pairs and tested for effects of environmental dissimilarity, biogeographical region and four alternative measures of ship‐borne species transport risk. We predicted that higher shipping between ports would decrease community dissimilarity, that the effect of shipping would be small compared to that of environment dissimilarity and shared biogeography, and that more complex shipping risk metrics (which account for ballast water and stepping‐stone spread) would perform better. Consistent with our hypotheses, community dissimilarities increased significantly with environmental dissimilarity and, to a lesser extent, decreased with ship‐borne species transport risks, particularly if the ports had similar environments and stepping‐stone risks were considered. Unexpectedly, we found no clear effect of shared biogeography, and that risk metrics incorporating estimates of ballast discharge did not offer more explanatory power than simpler traffic‐based risks. Overall, we found that shipping homogenizes eukaryotic communities between ports in predictable ways, which could inform improvements in invasive species policy and management. We demonstrated the usefulness of eDNA metabarcoding and dissimilarity regression for disentangling the drivers of large‐scale biodiversity patterns. We conclude by outlining logistical considerations and recommendations for future studies using this approach.

When are environmental DNA early detections of invasive species actionable? - Adam J. Sepulveda; Christine E. Dumoulin; Denise L. Blanchette; John McPhedran; Colin Holme; Nathan Whalen; Margaret E. Hunter; Christopher M. Merkes; Catherine A. Richter; Matthew E. Neilson; Wesley M. Daniel; Devin N. Jones; et al. (Journal of Environmental Management, 2023)

Grass variety selection of microbial community composition is associated with differences in soil CO2 emissions - M.E. Giles; S. Caul; D. King; S. Mitchell; A. Sim; R. Neilson; E. Paterson (Applied Soil Ecology, 2023)

Observations of parturition in humpback whales ( Megaptera novaeangliae ) and occurrence of escorting and competitive behavior around birthing females - Nicola Ransome; Lars Bejder; Micheline Jenner; Gavin Penfold; Violeta J. Brosig; Craig Kitson; Rebecca Skjothaug; Emma Neilson; Neil R. Loneragan; Joshua N. Smith (Marine Mammal Science, 2022)
Documented cases of cetacean births in the wild are rare. While there are currently no direct observations of a complete humpback whale birth, they are one of the few large whale species where observers have been present during a birthing event. We compiled eye‐witnessed accounts of all known humpback whale birthing events and found nine well‐documented cases globally (three published and six “new” unpublished). In two‐thirds of the accounts another “escort” whale was present and in close association with the birthing female, and of these, most cases involved multiple escorts ( n = 4). We describe details of birthing events, including mother, neonate and escort(s)’ behavior, neonate appearance, and discuss reasons for escort presence during parturition. We note that immediately postpartum: (1) blood and/or placenta were not always apparent during above water observations, (2) females often (but not always) supported calves at the surface, (3) constant travel and tail slapping were typical neonate behaviors, (4) two cases of temporary calf abandonment (

The gut microbiome–derived metabolite trimethylamine N-oxide modulates neuroinflammation and cognitive function with aging - Vienna E. Brunt; Thomas J. LaRocca; Amy E. Bazzoni; Zachary J. Sapinsley; Jill Miyamoto-Ditmon; Rachel A. Gioscia-Ryan; Andrew P. Neilson; Christopher D. Link; Douglas R. Seals (GeroScience, 2021)

Novel Murine Models of Cerebral Cavernous Malformations - Matthew R. Detter; Robert Shenkar; Christian R. Benavides; Catherine A. Neilson; Thomas Moore; Rhonda Lightle; Nicholas Hobson; Le Shen; Ying Cao; Romuald Girard; Dongdong Zhang; Erin Griffin; et al. (Angiogenesis, 2020)

Epidemiology and biology of physical activity and cancer recurrence - Christine M. Friedenreich; Eileen Shaw; Heather K. Neilson; Darren R. Brenner (Journal of Molecular Medicine, 2017)

Humpback whales interfering when mammal‐eating killer whales attack other species: Mobbing behavior and interspecific altruism? - Robert L. Pitman; Volker B. Deecke; Christine M. Gabriele; Mridula Srinivasan; Nancy Black; Judith Denkinger; John W. Durban; Elizabeth A. Mathews; Dena R. Matkin; Janet L. Neilson; Alisa Schulman‐Janiger; Debra Shearwater; et al. (Marine Mammal Science, 2017)
Humpback whales ( Megaptera novaeangliae ) are known to interfere with attacking killer whales ( Orcinus orca ). To investigate why, we reviewed accounts of 115 interactions between them. Humpbacks initiated the majority of interactions (57% vs . 43%; n = 72), although the killer whales were almost exclusively mammal‐eating forms ( MEKW s, 95%) vs . fish‐eaters (5%; n = 108). When MEKW s approached humpbacks ( n = 27), they attacked 85% of the time and targeted only calves. When humpbacks approached killer whales ( n = 41), 93% were MEKW s, and ≥87% of them were attacking or feeding on prey at the time. When humpbacks interacted with attacking MEKW s, 11% of the prey were humpbacks and 89% comprised 10 other species, including three cetaceans, six pinnipeds, and one teleost fish. Approaching humpbacks often harassed attacking MEKW s (≥55% of 56 interactions), regardless of the prey species, which we argue was mobbing behavior. Humpback mobbing sometimes allowed MEKW prey, including nonhumpbacks, to escape. We suggest that humpbacks initially responded to vocalizations of attacking MEKW s without knowing the prey species targeted. Although reciprocity or kin selection might explain communal defense of conspecific calves, there was no apparent benefit to humpbacks continuing to interfere when other species were being attacked. Interspecific altruism, even if unintentional, could not be ruled out.

Environmental influences on A tlantic bluefin tuna ( Thunnus thynnus ) catch per unit effort in the southern G ulf of S t. L awrence - Angelia S. M. Vanderlaan; Alex R. Hanke; Joël Chassé; John D. Neilson (Fisheries Oceanography, 2014)
The A tlantic bluefin tuna ( T hunnus thynnus ) population in the western A tlantic supports substantial commercial and recreational fisheries. Despite quota establishment and management under the auspices of the International Commission for the Conservation of A tlantic T unas, only small increases in population growth have been estimated. In contrast to other western bluefin tuna fisheries indices, contemporary estimates of catch per unit effort ( CPUE ) in the southern G ulf of S t. L awrence have increased rapidly and are at record highs. This area is characterized by the Cold Intermediate Layer ( CIL ) that is defined by waters in situ environmental variables on the bluefin tuna fishery CPUE using delta‐lognormal modelling and relatively extensive and consistent oceanographic survey data, as well as dockside monitoring and mandatory logbook data associated with the fishery. Although there is considerable spatial and temporal variation of water mass characteristics, the amount of available habitat in the southern G ulf of S t. L awrence (assuming a > 3°C thermal ambit) for bluefin tuna has been increasing. The percentage of the water column occupied by the CIL was a significant environmental variable in the standardization of CPUE estimates. There was also a negative relationship between the spatial extents of the CIL and the fishery. Properties of the CIL account for variation in the bluefin tuna CPUE and may be a factor in determining the amount of available feeding habitat for bluefin tuna in the southern G ulf of S t. L awrence.

Case–control study of lifetime alcohol consumption and endometrial cancer risk - Christine M. Friedenreich; Thomas P. Speidel; Heather K. Neilson; Annie R. Langley; Kerry S. Courneya; Anthony M. Magliocco; Linda S. Cook (Cancer Causes & Control, 2013)

Future Spruce Budworm Outbreak May Create a Carbon Source in Eastern Canadian Forests - Caren C. Dymond; Eric T. Neilson; Graham Stinson; Kevin Porter; David A. MacLean; David R. Gray; Michel Campagna; Werner A. Kurz (Ecosystems, 2010)

Interdecadal variation in seawater d13C and d18O recorded in fish otoliths - Ryan W. Schloesser; Jay R. Rooker; Patrick Louchuoarn; John D. Neilson; David H. Secord (Limnology and Oceanography, 2009)
Stable carbon (Δ 13 C) and oxygen (Δ 18 O) in the otolith cores of Atlantic bluefin tuna ( Thunnus thynnus ) vary temporally, with changes that quantitatively follow interdecadal variation in atmospheric and oceanic reservoirs. Both carbon and oxygen isotopic signatures vary significantly by year of birth over the range investigated (1947‐2006), with Δ 13 C decreasing and Δ 18 O increasing (‐2.56 × 10 −2 ‰ and 4.3 × 10 −3 ‰ yr −1 , respectively). The rate of change in otolith Δ 13 C was similar to reported rates of atmospheric Δ 13 C depletion, attributed to deforestation and the burning of fossil fuels (referred to as the Suess effect), suggesting a close link between atmospheric and oceanic carbon pools. Increases in otolith Δ 18 O were evident but less pronounced, with observed variation possibly attributable to changing salinity in the Atlantic Ocean. Otolith cores of bluefin tuna effectively track interdecadal trends and record past seawater Δ 13 C and Δ 18 O.

Selective recovery of the virus-vector trichodorid nematode Paratrichodorus anemones from soil samples by immunomagnetic capture - R. C. Holeva; D. J. F. Brown; R. H. C. Curtis; R. Neilson (European Journal of Plant Pathology, 2007)

Molecular identification of two stubby root nematode species - Ekaterini Riga; Eirini Karanastasi; C. Marcelo; G. Oliveira; R. Neilson (American Journal of Potato Research, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Predicting climate‐induced range shifts: model differences and model reliability - JOSHUA J. LAWLER; DENIS WHITE; RONALD P. NEILSON; ANDREW R. BLAUSTEIN (Global Change Biology, 2006)
Predicted changes in the global climate are likely to cause large shifts in the geographic ranges of many plant and animal species. To date, predictions of future range shifts have relied on a variety of modeling approaches with different levels of model accuracy. Using a common data set, we investigated the potential implications of alternative modeling approaches for conclusions about future range shifts and extinctions. Our common data set entailed the current ranges of 100 randomly selected mammal species found in the western hemisphere. Using these range maps, we compared six methods for modeling predicted future ranges. Predicted future distributions differed markedly across the alternative modeling approaches, which in turn resulted in estimates of extinction rates that ranged between 0% and 7%, depending on which model was used. Random forest predictors, a model‐averaging approach, consistently outperformed the other techniques (correctly predicting >99% of current absences and 86% of current presences). We conclude that the types of models used in a study can have dramatic effects on predicted range shifts and extinction rates; and that model‐averaging approaches appear to have the greatest potential for predicting range shifts in the face of climate change.

Global Warming and Extinctions of Endemic Species from Biodiversity Hotspots - JAY R. MALCOLM; CANRAN LIU; RONALD P. NEILSON; LARA HANSEN; LEE HANNAH (Conservation Biology, 2006)
Global warming is a key threat to biodiversity, but few researchers have assessed the magnitude of this threat at the global scale. We used major vegetation types (biomes) as proxies for natural habitats and, based on projected future biome distributions under doubled‐CO 2 climates, calculated changes in habitat areas and associated extinctions of endemic plant and vertebrate species in biodiversity hotspots. Because of numerous uncertainties in this approach, we undertook a sensitivity analysis of multiple factors that included (1) two global vegetation models, (2) different numbers of biome classes in our biome classification schemes, (3) different assumptions about whether species distributions were biome specific or not, and (4) different migration capabilities. Extinctions were calculated using both species‐area and endemic‐area relationships. In addition, average required migration rates were calculated for each hotspot assuming a doubled‐CO 2 climate in 100 years. Projected percent extinctions ranged from

Decadal-Scale Climate and Ecosystem Interactions in the North Pacific Ocean - Arthur J. Miller; Fei Chai; Sanae Chiba; John R. Moisan; Douglas J. Neilson (Journal of Oceanography, 2004)

Estimated migration rates under scenarios of global climate change - Jay R. Malcolm; Adam Markham; Ronald P. Neilson; Michael Garaci (Journal of Biogeography, 2002)
Aim Greenhouse‐induced warming and resulting shifts in climatic zones may exceed the migration capabilities of some species. We used fourteen combinations of General Circulation Models (GCMs) and Global Vegetation Models (GVMs) to investigate possible migration rates required under CO 2 ‐doubled climatic forcing. Location Global. Methods Migration distances were calculated between grid cells of future biome type x and nearest same‐biome‐type cells in the current climate. In `base‐case' calculations, we assumed that 2 × CO 2 climate forcing would occur in 100 years, we used ten biome types and we measured migration distances as straight‐line distances ignoring water barriers and human development. In sensitivity analyses, we investigated different time periods of 2 × CO 2 climate forcing, more narrowly defined biomes and barriers because of water bodies and human development. Results In the base‐case calculations, average migration rates varied significantly according to the GVM used (BIOME3 vs. MAPSS), the age of the GCM (older‐ vs. newer‐generation GCMs), and whether or not GCMs included sulphate cooling or CO 2 fertilization effects. However, high migration rates (≥ 1000 m year −1 ) were relatively common in all models, consisting on average of 17% grid cells for BIOME3 and 21% for MAPSS. Migration rates were much higher in boreal and temperate biomes than in tropical biomes. Doubling of the time period of 2 × CO 2 forcing reduced these areas of high migration rates to c . 12% of grid cells for both BIOME3 and MAPSS. However, to obtain migration rates in the Boreal biome that were similar in magnitude to those observed for spruce when it followed the retreating North American Glacier, a radical increase in the period of warming was required, from 100 to >1000 years. A reduction in biome area by an order of magnitude increased migration rates by one to three orders of magnitude, depending on the GVM. Large water bodies and human development had regionally important effects in increasing migration rates. Main conclusions In conclusion, evidence from coupled GCMs and GVMs suggests that global warming may require migration rates much faster than those observed during post‐glacial times and hence has the potential to reduce biodiversity by selecting for highly mobile and opportunistic species. Several poorly understood factors that are expected to influence the magnitude of any such reduction are discussed, including intrinsic migrational capabilities, barriers to migration, the role of outlier populations in increasing migration rates, the role of climate in setting range limits and variation in species range sizes.

Longidorus cretensis n. sp. (Nematoda: Longidoridae) from a vineyard infected with a foliar `yellow mosaic' on Crete, Greece - E.A. Tzortzakakis; V. Peneva; M. Terzakis; R. Neilson; D.J.F. Brown (Systematic Parasitology, 2001)

Criconematidae (Nematoda) from oak forests in two nature reserves in Russia - V. Peneva; R. Neilson; B. Boag; D.J.F. Brown (Systematic Parasitology, 2000)

Spatial variability of soil total C and N and their stable isotopes in an upland Scottish grassland - C.A. Marriott; G. Hudson; D. Hamilton; R. Neilson; B. Boag; L.L. Handley; J. Wishart; C.M. Scrimgeour; D. Robinson (Plant and Soil, 1997)

An assessment of morphometric variability between populations of Longidorus vineacola Sturhan & Weischer, 1964 (Nematoda: Longidoridae) and morphologically related species - D.J.F. Brown; R. Neilson; T. Connolly; B. Boag (Systematic Parasitology, 1997)